Sexual variation in the inter-triradial distance of the palm among Bengali Hindu population of Kolkata, India - Banerjee, Ritwik; Das, Manashi (Anthropological Review, 2023)
Palm prints are one of the most important forensic tools for human identification in medico-legal investigation. Palm prints are often used for forensic sex estimation to narrow down the pool of suspects through a process of elimination. The aim of this study was to test whether a novel approach of sex estimation from palmar inter-triradial distances previously posited by Badiye and colleagues [Journal of Forensic and Legal Medicine, 2019; 65(March):22–26] can be used as a primary tool for forensic sexing. For this study the bilateral palm prints from 200 Bengali Hindu adults (100 male, 100 female) were collected using traditional ink printing method and were analysed. Descriptive statistics were presented in tables and linear discriminant analysis was conducted to estimate the extent of sexual dimorphism in the inter-triradial distances and to find out variables with the strongest sex discriminating potential. Binary logistic regression analysis (BLR) was performed to derive sex estimation equations. Sexual dimorphism has been found to be statistically significant (p< 0.001) using linear discriminant analysis with a sexing accuracy of 79.0 percent for the left and 79.5 percent for the right palm. Distance between a and t triradius has been found to be the most influential on this model followed by the combined abcd-t distance. For the BLR analysis, the correct classification percentage was found to be the highest on the a-t distance of the right palm with a success rate of 80.5 percent which is closely followed by the combined abcd-t distance which has a classification success rate of 80.0 percent for the right palm. The present study has concluded that, inter-triradial distance of the palm is fairly dimorphic sexually but can only be used as a supplementary tool in inference of sex for medico-legal investigation. Due to a higher accuracy, the distance between a and t triradius has been proposed to be used instead of combined abcd-t distance which was suggested in the original study conducted by Badiye and colleagues (2019).